EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN SMART TV DALAM MENINGKATKAN PEMAHAMAN BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMAN 1 YOSOWILANGUN - David Ainun Nugroho; Sofyan Rofi; Hairul Huda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of using Smart TV learning media in improving students' learning comprehension in Islamic Religious Education (PAI) at SMAN 1 Yosowilangun. This research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The subjects of this study included PAI teachers, the curriculum coordinator, the infrastructure coordinator, and students of class XII. The results show that the use of Smart TV learning media effectively improves students' learning comprehension in PAI subjects. Smart TV creates an interactive, attractive, and non-monotonous learning atmosphere that enhances student motivation, participation, and cognitive engagement. Teachers apply the MODERAT strategy (Muhasabah, Observasi, Mendalami materi, Elaborasi, dan Ruang Aktualisasi) which integrates Smart TV as the primary medium for planning, creating, and presenting student projects. The supporting factors include the availability of adequate facilities and teachers' digital competence, while the main obstacle is internet connectivity. Overall, Smart TV is a relevant and effective digital innovation for improving the quality of PAI learning in the digital era. Keywords: Smart TV, Learning Media, Learning Comprehension, Islamic Religious Education